La práctica lúdica y su influencia en el aprendizaje de la matemática, en los alumnos de primero y segundo ciclo del centro de educación básica “Dr. Néstor Mogollón López” del cantón La Maná. periodo lectivo: 2011-2012 - Molina Esquivel, Jessica Lilián (2012)
This investigative work was aimed on the process of learning mathematics in order to diagnose knowledge by using materials, math games and development of ludic activities. In the development of chapter I, it was known the theoretical and fundamental categories. Inside this chapter, the concepts of the ludic practice in mathematics are described. During the course of chapter II, the technique of the survey was carried out to students and teachers from the institution. According to the information, it was showed the deficient motivation in math classes; and it was used the active, intuitive, analogical or comparative, deductive-inductive methods for teaching and learning of mathematics.